SOLUTIONS TO OVERCOME HORMONAL CHANGES IN PREMENOPAUSE AND MENAPOUSE IN CHIBA MUSLIM RECITATION IN CHIBA – JAPAN THROUGH EDUCATION - Indrayani, Triana; Aenurida, Aenurida; Novita, Vera; Pibriani, Pibriani; Marlina, Ela; Aprillianti, Lia; Humaeroh, Yayu (Yayasan Education and Social Center, 2025)
Menopause and premenopause are natural transition phases experienced by women with significant hormonal changes. This condition is often accompanied by symptoms such as hot flashes, sleep disturbances, mood swings, and an increased risk of osteoporosis and cardiovascular disease. This community service program aims to provide comprehensive knowledge and solutions in dealing with hormonal disorders in premenopausal and menopausal women through educational approaches, non-pharmacological therapies (complementary therapies), and lifestyle changes. The methods used in this activity are the preparation and submission of proposals, counselling, questions and answers, evaluations and door prizes. The materials provided include health seminars, healthy lifestyle training, and medical consultations involving health professionals. The results of the program showed that participants had increased knowledge about menopause and how to cope with hormonal changes in non-pharmacological ways (complementary therapy). In conclusion, multidisciplinary approaches in complementary lifestyle and parenting education and interventions can help women better manage menopausal symptoms, improve quality of life, and reduce the negative impact of hormonal changes that occur. Therefore, it is important to continue to develop similar programs to help more women cope with this transition optimally.